Brexit and beyond : rethinking the futures of Europe - Martill, Benjamin, 1988-; Staiger, Uta, 1976- (UCL Press, 2018)
"Brexit will have significant consequences for the country, for Europe, and for global order. And yet much discussion of Brexit in the UK has focused on the causes of the vote and on its consequences for the future of British politics. This volume examines the consequences of Brexit for the future of Europe and the European Union, adopting an explicitly regional and future-oriented perspective missing from many existing analyses. Drawing on the expertise of 28 leading scholars from a range of disciplines, 'Brexit and Beyond' offers various different perspectives on the future of Europe, charting the likely effects of Brexit across a range of areas, including institutional relations, political economy, law and justice, foreign affairs, democratic governance, and the idea of Europe itself. Whilst the contributors offer divergent predictions for the future of Europe after Brexit, they share the same conviction that careful scholarly analysis is in need -- now more than ever -- if we are understand what lies ahead for the EU."--Provided by publisher